2022
DOI: 10.1177/13548166221102806
|View full text |Cite
|
Sign up to set email alerts
|

Does firm strategy influence corporate social responsibility and firm performance? Evidence from the tourism industry

Abstract: In this study, we explore whether cost leaders and differentiators assume different positions in terms of corporate social responsibility (CSR) engagement. Furthermore, we deepen the investigation by examining whether shareholders appreciate cost leaders or differentiators' CSR engagement which bears implications for the firms and stockholders. The data concerning CSR, firm strategy, and board characteristics for all the companies belonging to the hospitality, tourism, and airline industry between 2013 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 92 publications
2
15
0
Order By: Relevance
“…Similarly, in their recent study analysing data concerning CSR, firm strategy, and board characteristics for all companies belonging to the hospitality, tourism, and airline industries between 2013 and 2019, Uyar et al (2022) confirmed that cost leadership is significantly associated with composite CSR performance and governance performance, but not with environmental and social performance. They also reported that moderation analysis revealed that cost leadership does not moderate the association between CSR performance in all dimensions and firm value.…”
Section: Cost Leadership Strategymentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, in their recent study analysing data concerning CSR, firm strategy, and board characteristics for all companies belonging to the hospitality, tourism, and airline industries between 2013 and 2019, Uyar et al (2022) confirmed that cost leadership is significantly associated with composite CSR performance and governance performance, but not with environmental and social performance. They also reported that moderation analysis revealed that cost leadership does not moderate the association between CSR performance in all dimensions and firm value.…”
Section: Cost Leadership Strategymentioning
confidence: 84%
“…Despite prior studies attempting to explore the link between firm strategy and CSR engagement (Xu and Liu, 2017; Uyar et al. , 2022), whether CSR fosters firm strategy or not has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…First, as CSR is increasingly becoming part of business strategy, whether cost leaders and differentiators are integrating CSR into their corporate strategy is a problem to be resolved from both shareholders' and stakeholders' perspectives. Second, the existing literature on business strategy and CSR nexus is very scarce and limited to specific sectors or countries such as tourism (Uyar et al, 2022) and the US (Peng, 2020; Yuan et al, 2020) and draws on composite CSR indicator; hence, we extend those studies drawing on an international sample and sub‐indicators of ESG pillars. Third, by relating each business strategy follower's CSR uptake to the firm value which is a missing link in Peng (2020) and Yuan et al (2020), we provide insight into shareholder reaction to the business strategy‐CSR coupling.…”
Section: Discussionmentioning
confidence: 98%
“…First, as CSR is increasingly becoming part of business strategy, whether cost leaders and differentiators are integrating CSR into their corporate strategy is a problem to be resolved from both shareholders' and stakeholders' perspectives. Second, the existing literature on business strategy and CSR nexus is very scarce and limited to specific sectors or countries such as tourism (Uyar et al, 2022) and the US (Peng, 2020;Yuan et al, 2020) No precise relationship is detected for either strategy follower in terms of addressing shareholders' concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the study also implies that the policymakers, including local government and tourism departments, regulate environmental protection policies (Uyar et al , 2022). All stakeholders, including travel agencies, scenic sports and management of the tourist destination, should know about environmental protection policies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%